Chromobox 7/8 serve as independent indicators for glioblastoma via promoting proliferation and invasion of glioma cells - Zheng, Zong-Qing; Yuan, Gui-Qiang; Kang, Na-Ling; Nie, Qian-Qian; Zhang, Guo-Guo; Wang, Zhong (Frontiers in Neurology, 2022)
Background The chromobox family, a critical component of epigenetic regulators, participates in the tumorigenesis and progression of many malignancies. However, the roles of the CBX family members (CBXs) in glioblastoma (GBM) remain unclear. Methods The mRNA expression of CBXs was analyzed in tissues and cell lines by Oncomine and Cancer Cell Line Encyclopedia (CCLE). The differential expression of CBXs at the mRNA level was explored in The Cancer Genome Atlas (TCGA) and Chinese Glioma Genome Atlas (CGGA) databases with the “beeswarm” R package. The protein expression of CBXs in GBM was further examined on Human Protein Atlas (HPA). The correlations between CBXs and IDH mutation and between CBXs and GBM subtypes were investigated in the TCGA portal and CGGA database with the “survminer” R package. The alteration of CBXs and their prognostic value were further determined via the cBioPortal and CGGA database with the “survival” R package. The univariate and multivariate analyses were performed to screen out the independent prognostic roles of CBXs in the CGGA database. Cytoscape was used to visualize the functions and related pathways of CBXs in GBM. U251 and U87 glioma cells with gene intervention were used to validate the role of CBX7/8 in tumor proliferation and invasion. Proliferation/invasion-related markers were conducted by Western blot and immunostaining. Results CBXs presented significantly differential expressions in pan-cancers. CBX2/3/5/8 were upregulated, whereas CBX6/7 were downregulated at mRNA level in GBM of TCGA and CGGA databases. Similarly, high expression of CBX2/3/5 and low expression of CBX6/8 were further confirmed at the protein level in the HPA. CBX2/6/7 were positively correlated with IDH mutation and CBX1/2/4/5/8 were closely related to GBM subtypes. CBX7 and CBX8 presented the independent prognostic factors for GBM patient survival. GO and KEGG analyses indicated that CBXs were closely related to the histone H3-K36, PcG protein complex, ATPase, and Wnt pathway. The overexpression of CBX7 and underexpression of CBX8 significantly inhibited the proliferation and invasion of glioma cells in vivo and in vitro. Conclusion Our results suggested that CBX7 and CBX8 served as independent prognostic indicators that promoted the proliferation and invasion of glioma cells, providing a promising strategy for diagnosing and treating GBM.